2001
DOI: 10.1159/000048102
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment Does Not Alter Lower Limb Asymmetry in Children with Russell-Silver Syndrome

Abstract: Background: Growth hormone (GH) treatment has been proven to have a beneficial effect on growth in children with Russell-Silver syndrome (RSS). Methods: We describe 7 prepubertal children with RSS and lower limb asymmetry treated with GH for 3 years. Results: There was a significant increase in height without any significant change in the asymmetry. Conclusions: We conclude that the rapid growth acceleration to GH treatment does not alter the lower limb asymmetry in children with RSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Limb asymmetry can affect the arms, legs or both. In seven patients with clinically diagnosed SRS, limb length discrepancy was not significantly affected by GH treatment 144 . Limb lengthening surgery performed to equalize limb lengths in patients with SRS has shown positive results 145 .…”
Section: Neurocognitive Problemsmentioning
confidence: 80%
“…Limb asymmetry can affect the arms, legs or both. In seven patients with clinically diagnosed SRS, limb length discrepancy was not significantly affected by GH treatment 144 . Limb lengthening surgery performed to equalize limb lengths in patients with SRS has shown positive results 145 .…”
Section: Neurocognitive Problemsmentioning
confidence: 80%
“…Our hypothesis of a mosaicism with a higher degree of ICR1 hypomethylation at the shorter body side could not be confirmed in bilaterally-obtained probes of oral mucosa and skin. Our observation renders it unlikely that the postnatal persistence of asymmetric growth in the adolescent SRS patients [4] is due to a persisting long side-short side ICR1 hypomethylation difference. Epigenetic mechanisms causing body asymmetry may be restricted to the intrauterine development.…”
Section: Discussionmentioning
confidence: 94%
“…It is diagnosed on the basis of the combination of intrauterine growth retardation, severe short stature, characteristic triangular face, relative macrocephaly, body asymmetry, underweight, and several minor abnormalities [1-3]. The relative limb length differences in asymmetric SRS patients are present at birth and stay stable during the growth process [4]. Short stature in SRS can be treated with pharmacological doses of recombinant growth hormone [5].…”
Section: Introductionmentioning
confidence: 99%
“…Information about the possible adverse events during GH treatment in children with SRS is also limited. In a study (44), it was shown that GH treatment does not increase skeletal asymmetry. On the other hand, there is concern about development of insulin resistance in children with SRS treated with GH (38).…”
Section: Silver-russell Syndromementioning
confidence: 99%